Penguatan Manajemen Keuangan Syariah Bagi Pengelola Badan Usaha Milik Desa (BUMDes) - Jenita Jenita; Rozi Andrini; Hertina Hertina; Zuraidah Zuraidah; Try Kurnia Ningsih (MENARA RIAU, 2023)
The purpose of this service is to increase the understanding of Village-Owned Enterprises (BUMDes) managers regarding Islamic financial management and increase the motivation of BUMDes managers to carry out Islamic financial management in BUMDes management. The strategy used in the implementation of community service is to start with conducting a situation analysis, then the service team determines the method of solving the problem, namely providing understanding and motivation regarding Islamic financial management in the form of socialization. The target audience of this service is the manager of the Taiba Smart BUMDes. The results of this community service activity note that the management of Taiba Smart BUMDes has not implemented sharia financial management in operations because Taiba Smart BUMdes in general still use conventional systems. From the socialization results, it is known that the understanding of BUMDes management regarding Islamic financial management has increased. Sharia financial management that can be carried out by BUMDes Taiba Smart is to make BUMDes financial management by contracts and transactions in the Islamic economy. In the microfinance business, cooperation contracts (mudharabah and musyarakah) can be used, buying and selling (murabahah, salam, istishna), services (wakalah, kafalah, hiwalah, wadiah, rahn, qardh). For trading businesses, murabahah, salam and istishna sale and purchase agreements can be used. For the rental business, you can use an ijarah contract. The motivation given showed the increasing desire of participants to apply Islamic financial management to the Taiba Smart BUMDes operations.